Oral microbiome: A paradigm shift in dental diagnosis - Megantoro, Aryo; Alphianti, Likky T.; Gunawan, Paulina N.; Bachtiar, Endang W.; Bachtiar, Boy M. (Narra X, 2025)
For decades, the diagnosis of oral diseases primarily relied on clinical symptoms presented by patients. This traditional approach, which included visual inspection, palpation, and assessment of discomfort, provided limited insights into the underlying microbiological factors contributing to oral diseases. Recent studies have identified specific microorganisms believed to play pivotal roles in oral disease development, particularly in conditions such as dental caries, periodontal disease, and pulpitis. The challenge lies in the dynamic nature of the oral microenvironment, where the microbial community can shift rapidly due to changes in diet, hygiene practices, and overall health, complicating attempts to establish direct causative links between specific pathogens and oral diseases. The aim of this study was to explore the role of the oral microbiome in advancing dental diagnostics and to assess how integrating microbial analysis can improve early detection and personalized treatment of oral diseases. Research into the oral microbiome has brought about a paradigm shift in understanding dental diagnostics. Advances in molecular biology techniques, such as next-generation sequencing (NGS) and polymerase chain reaction (PCR), have enabled more detailed examination of microbial communities within the oral cavity. This shift from a purely symptom-based diagnostic approach to one that incorporates microbial analysis represents a significant advancement in dental care. For instance, identifying specific bacterial profiles associated with caries could facilitate the implementation of personalized preventive measures, such as tailored oral hygiene regimens or dietary recommendations. Moreover, integrating microbiological data into clinical practices could lead to improved diagnostics for conditions that are traditionally difficult to assess. By adopting a more comprehensive view that includes microbial assessments, clinicians can better understand the interplay between oral microbiota and systemic health, as oral diseases are often linked to broader health issues. Another challenge is that this approach requires interdisciplinary collaboration among dental practitioners, microbiologists, and public health experts. This collaboration is essential to translate abstract microbiological findings into practical diagnostic indicators that can be utilized in clinical settings. Furthermore, with the advent of new technologies, maintaining accurate interpretations of microbiome data presents another layer of complexity, as variations in sample collection, processing, and analysis can lead to differing results. In summary, the elevated role of the oral microbiome in dental diagnostics marks a significant transition from traditional, symptom-focused approaches to more holistic methodologies that consider the underlying microbial communities. By leveraging advanced technologies, dental practitioners can enhance their diagnostic capabilities, leading to improved outcomes for patients suffering from various oral diseases.